2022
DOI: 10.1002/jwmg.22325
|View full text |Cite
|
Sign up to set email alerts
|

Piping plover chick ecology following landscape‐level disturbance

Abstract: Population declines of disturbance‐dependent species due to suppression of natural disturbances are realized across ecosystems. The piping plover (Charadrius melodus; plover), a disturbance‐dependent and conservation‐reliant shorebird that nests on sandy beaches and barrier islands on the Atlantic Coast, was listed under the United States Endangered Species Act in 1986. In 2012, Hurricane Sandy landed on Fire and Westhampton islands, barrier island nesting sites for plovers in New York, USA. Hurricane Sandy wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…We used the autumn and winter data following the plover breeding season because it better represented fox abundance with respect to winter die-offs, kit production, and territory changes that may happen between plover breeding seasons (Black 2021). We also included plover nesting density (pairs/ha of nesting habitat, summarized for the 4 sites in the study area; Walker et al 2019) and days since hatch as additional variables to control for known variation (Robinson et al 2023). We standardized all variables prior to their inclusion in the model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the autumn and winter data following the plover breeding season because it better represented fox abundance with respect to winter die-offs, kit production, and territory changes that may happen between plover breeding seasons (Black 2021). We also included plover nesting density (pairs/ha of nesting habitat, summarized for the 4 sites in the study area; Walker et al 2019) and days since hatch as additional variables to control for known variation (Robinson et al 2023). We standardized all variables prior to their inclusion in the model.…”
Section: Methodsmentioning
confidence: 99%
“…We used a modified Dail‐Madsen model (Dail and Madsen 2011) described by Robinson et al (2023) to estimate pre‐fledging (0–25 days after hatch) chick survival (φ $\varphi $) each year from 2015–2018. This model approximates a young survival model (Lukacs et al 2004) and uses counts of chicks in known broods at regular intervals to estimate individual chick survival.…”
Section: Methodsmentioning
confidence: 99%
“…Focal surveys were conducted by randomly selecting individuals to record foraging behaviors and the number of pecks. Previous research has indicated that the peck rate can be representative of the intake or foraging rate of a plover when the prey of the plover is too small to identify during the survey [30,31]. Focal surveys were three minutes per individual, based on a prior study of foraging behavior, which included a two-minute survey per foraging individual [32].…”
Section: Methodsmentioning
confidence: 99%